SEMIOTIKA KOMUNIKASI VISUAL: SISTEM PEMAKNAAN IKLAN ROKOK U MILD VERSI SEPANJANG JALAN KENANGAN - Winata Faturahman (Universitas Serang Raya, 2017)
Advertisement is a mass media that serves to offer and promote products. Ads must have a massage that consumers can understand so they can know the product. Visual is on medium to communicate the ads massage and more effective than ads by voice. Visual communication makes a product can reach a wider consumer because consumrs can see the product offered. U mild is a cigarette product in Indonesia. U mild effort to reach consumers to present ads on television. Semiotic is a science that is closely related to the communication of an advertisement. In semiotic there is a meaning system that can be used to examine the communication of an advertisement massage. The meaning system can discribe the visual communication dilivered an advertisement, in this case is how the meaning system of U mild cigarette advertisement